2009
DOI: 10.1182/blood-2009-03-202267
|View full text |Cite
|
Sign up to set email alerts
|

A murine model for induction of long-term immunologic tolerance to factor VIII does not require persistent detectable levels of plasma factor VIII and involves contributions from Foxp3+ T regulatory cells

Abstract: Under certain instances, factor VIII (FVIII) stimulates an immune response, and the resulting neutralizing antibodies present a significant clinical challenge. Immunotherapies to re-establish or induce longterm tolerance would be beneficial, and an in-depth knowledge of mechanisms involved in tolerance induction is essential to develop immune-modulating strategies. We have developed a murine model system for studying mechanisms involved in induction of immunologic tolerance to FVIII in hemophilia A mice. We

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 41 publications
1
46
0
Order By: Relevance
“…In this study, we used a LV system to deliver the transgene to neonatal mice by an intravascular route where because of immune tolerance the formation of inhibitory antibodies or host immune responses against transduced cells would be extremely unlikely. [46][47][48] This allowed us to directly compare FVIII expression from FVIII constructs containing various B domains from non-codon-optimized and codon-optimized cDNA sequences without the confounding effect of variable immune responses against human FVIII, neo epitopes and the Fugu B domain. The dramatic increase in the observed level of secreted FVIII from codon optimized cDNA sequences in this model system will now need to be validated in immune competent animals but open the possibility of development of safer, more efficacious vectors for gene therapy of hemophilia A.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we used a LV system to deliver the transgene to neonatal mice by an intravascular route where because of immune tolerance the formation of inhibitory antibodies or host immune responses against transduced cells would be extremely unlikely. [46][47][48] This allowed us to directly compare FVIII expression from FVIII constructs containing various B domains from non-codon-optimized and codon-optimized cDNA sequences without the confounding effect of variable immune responses against human FVIII, neo epitopes and the Fugu B domain. The dramatic increase in the observed level of secreted FVIII from codon optimized cDNA sequences in this model system will now need to be validated in immune competent animals but open the possibility of development of safer, more efficacious vectors for gene therapy of hemophilia A.…”
Section: Discussionmentioning
confidence: 99%
“…32 In addition, retroviral gene transfer to activated B cells induced tolerance by stimulating an endogenous population of Tregs. 33 Neonatal gene transfer into HemA mice 34 and mucopolysaccharidosis I mice with transient immunomodulation 35 prevented antibody production with increase in Treg population.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, F.VIII seems to be naturally more immunogenic than F.IX, since hemophilia A patients develop inhibitors at about 5-6 times the rate of hemophilia B patients during recombinant protein therapy. Conversely, other studies have suggested that tolerance to F.VIII following hepatic gene transfer with LV may occur or persist in the absence of transgene expression (259). However, these mice were transduced as neonates; the protocol was not tolerogenic in older mice or with non-hepatic delivery routes.…”
Section: Gene Therapies For Hemophlia Amentioning
confidence: 99%